Evaluating the wear and friction characteristics of heat-treated and as-cast ex-situ Al-Si7Mg/SiC composites under lubricated conditions - Vishal Mehta; Anand Joshi; Prathamesh Potdar; Mayur Sutaria (Discover Materials)
Abstract The present study investigates wear and friction characteristics of Al-Si7Mg aluminum matrix composites (AMCs) reinforced with silicon carbide (SiC) in as-cast and heat-treated conditions, with a focus upon the influence of lubrication. The composites were developed by an ex-situ technique using a stir casting process. Tribological performance was evaluated using a pin-on-disk tribotester, varying the flow rate of lubricant, applied load, and sliding distance. To identify the significance of variables on wear and COF, ANOVA analysis was carried out. The findings showed that heat-treated composites outperformed as-cast samples with regard to wear resistance and COF, which was attributed to better interfacial bonding between the SiC particles and the Al-Si7Mg matrix. The predominant wear mechanisms were further validated by SEM-Scanning Electron Microscopy analysis of worn-out faces, which showed that heat-treated samples showed mild delamination and as-cast samples showed severe abrasive wear. Lubrication played an important role in decreasing wear by minimizing metal-to-metal contact and enhancing surface morphology. X-ray Diffraction (XRD) analysis recognized the primary phases, including aluminum (Al), silicon carbide (SiC), and a minor formation of aluminum carbide (Al₄C₃) in the composites. The findings highlight the potential of Al-Si7Mg/SiC AMC as favorable materials for applications in automotive, where reduced wear and lower COF are critical, such as in engine components, brake systems, and transmission parts. The tribological performance of Al-Si7Mg/SiC composites was demonstrated to be greatly improved by the combination of heat treatment and lubrication, offering a comprehensive understanding of their behavior in real-world applications.